(untitled) (Herald of the National Children’s Medical Center, 2024)
The problem of treatment of cystic dilation of the bile ducts (cystic fibrosis) In children, hepatobiliary surgery is still widely discussed. The treatment of this anomaly is exclusively surgical. There is no consensus among the authors on the methods of surgical treatment for CROUP in children.